2004
DOI: 10.1017/s0950268803001717
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and population genetics of Salmonella subspecies diarizonae in sheep in Norway and Sweden

Abstract: Fifty-four isolates of Salmonella enterica subsp. diarizonae (IIIb) in Norway, Sweden, England, the United States, France and Australia were characterized by pulsed-field gel electrophoresis (PFGE). This study focuses on serovar 61:k:1,5,(7) [S. IIIb 61:k:1,5,(7)] isolated from sheep. Digestion of the bacterial DNA with restriction enzyme XhaI yielded 15 distinct PFGE profiles comprising 12-16 fragments in the range 48.5-630.5 kbp. Four different profiles were identified in Norwegian sheep isolates and a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The PFGE subtyping method was very discriminative for this serotype, as reported previously in Norwegian and Swedish sheep [6].…”
supporting
confidence: 79%
See 2 more Smart Citations
“…The PFGE subtyping method was very discriminative for this serotype, as reported previously in Norwegian and Swedish sheep [6].…”
supporting
confidence: 79%
“…Thorough investigations revealed that nine of the ten isolates had grown on sheep blood agar from the same manufacturer and that the batch number was similar for three cases. Moreover, SIIIb 61:k:1,5,7 infections in European sheep flocks had previously been described [6].…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…diarizonae 61:k:1,5,(7) strains of which 17 were found in only one animal. Alvseike et al (2004) found only 15 distinct XbaI patterns among 54 S. enterica subsp. diarizonae belonging to different serotypes.…”
Section: Discussionmentioning
confidence: 98%
“…Subspecies IIIa and IIIb are considered reptile associated, and they colonize the reptilian intestinal tract asymptomatically and are excreted in feces (6,11,49,58). Both subspecies IIIa and IIIb can cause disease in various warm-blooded vertebrates, including humans, domestic poultry, sheep, wild birds, and cats (1,2,18,50). Subspecies IIIa and IIIb are observed as the cause of disease in humans, especially in the young and in immunocompromised individuals.…”
mentioning
confidence: 99%